2018
DOI: 10.1016/j.celrep.2018.03.094
|View full text |Cite
|
Sign up to set email alerts
|

TMEM150C/Tentonin3 Is a Regulator of Mechano-gated Ion Channels

Abstract: SUMMARY Neuronal mechano-sensitivity relies on mechanogated ion channels, but pathways regulating their activity remain poorly understood. TMEM150C was proposed to mediate mechano-activated current in proprioceptive neurons. Here, we studied functional interaction of TMEM150C with mechano-gated ion channels from different classes (Piezo2, Piezo1, and the potassium channel TREK-1) using two independent methods of mechanical stimulation. We found that TMEM150C significantly prolongs the duration of the mechano-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 52 publications
1
70
1
Order By: Relevance
“…Mutations that affect inactivation in either channel are linked to disease, and thus the timing of this process has physiological importance (9,(62)(63)(64). Inactivation is influenced by cellular factors and is thought to involve a hydrophobic gate formed primarily by the inner helices plus other regions including the extracellular cap (23,61,(65)(66)(67)(68). Whether inactivation is governed by changes in plasma membrane properties is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations that affect inactivation in either channel are linked to disease, and thus the timing of this process has physiological importance (9,(62)(63)(64). Inactivation is influenced by cellular factors and is thought to involve a hydrophobic gate formed primarily by the inner helices plus other regions including the extracellular cap (23,61,(65)(66)(67)(68). Whether inactivation is governed by changes in plasma membrane properties is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…HEK293T ΔP1 , N2A ΔP1 (27,38) and ND7/23 cells were cultured using standard procedures. Duck-Piezo2-pMO and Mouse-Piezo1-pMO were described previously (67). Squirrel Piezo2 was amplified from squirrel DRG cDNA and deposited into the GenBank database (accession no.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if this increase in cell mechanosensitivity occurs in other cell types, we examined the effect of TACAN expression on mechanically-evoked currents in COS-7 and HEK293 cells (HEK293/17) ( Figures S3A-S3D), which are commonly used to study MSCs (Anderson et al, 2018;Coste et al, 2010;Li Fraine et al, 2017). In MOCK-transfected COS7 cells, we observed the presence of endogenous MSCs ( Figure S3A, left panel) with a low activation threshold, often as low as -5 mm Hg (mean activation threshold: -21.3 ± 1.6 mm Hg, n=97), consistent with previous reports (Sharif-Naeini et al, 2009).…”
Section: Tacan Expression Increases Mechanically-evoked Currents In Hmentioning
confidence: 99%
“…It was recently suggested that some candidate MSCs may act as permissive factors that promote the expression or membrane targeting of the endogenous channel (Anderson et al, 2018;Dubin et al, 2017). Alternatively, they may need additional subunits to form a functional ion channel.…”
Section: Tacan Forms An Ion-conducting Channel When Reconstituted In mentioning
confidence: 99%
“…Inactivation modulates mechanical sensitivity and endows Piezos with the ability to function as frequency filters of repetitive stimuli, though the physiological implications of these findings have yet to be explored (Lewis et al, 2017;Lewis and Grandl, 2015). Regulation of inactivation occurs through many mechanisms, including alternative splicing, pH, temperature, divalent ions, osmotic swelling, co-expression of other membrane proteins, membrane lipid composition, and G-protein-coupled pathways (Anderson et al, 2018;Bae et al, 2015;Dubin et al, 2012;Eijkelkamp et al, 2013;Gottlieb and Sachs, 2012;Jia et al, 2013;Romero et al, 2019;Szczot et al, 2017;Zheng et al, 2019b). Moreover, mutations in both Piezo1 and Piezo2 have been identified in human patients diagnosed with xerocytosis and distal arthrogryposis that cause a gain-of-function phenotype by slowing inactivation, indicating that normal physiology requires inactivation to be intact (Albuisson et al, 2013;Bae et al, 2013;Coste et al, 2013;Zarychanski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%